2013
DOI: 10.5901/ajis.2013.v2n9p278
|View full text |Cite
|
Sign up to set email alerts
|

Legal Status of a Minor in Giving Consent to Treatment from the Perspective of the Malaysian Child Act 2001

Abstract: Patient's autonomy to make his own decision is an ethical principle that has been interpreted into the legal concept of consent. Consent to medical treatment is a very fundamental aspect in medical law as it can be regarded as an acknowledgment that a patient has the right to make his own decision on what he wants to be done to his body. In the area of consent, capacity of the patient to make decision plays an important role. Capacity from the context of a patient's age is one of the factors that needs to be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…On the other hand, Section 2 (1) The Guardianship of the Infant Act 1961 defines 'child' or 'infant' as a person who has not attained majority. Besides, Subsection 2 (a): i) further explains that for this act, every person professing the religion of Islam shall be deemed to have attained his majority when he shall have completed his age of eighteen (18) years and not before; ii) every other person shall be deemed to have attained his majority when he shall have completed his age of 21 years not before [16].…”
Section: Volatility Uncertainty Complexity and Ambiguity (Vuca) On Ch...mentioning
confidence: 99%
“…On the other hand, Section 2 (1) The Guardianship of the Infant Act 1961 defines 'child' or 'infant' as a person who has not attained majority. Besides, Subsection 2 (a): i) further explains that for this act, every person professing the religion of Islam shall be deemed to have attained his majority when he shall have completed his age of eighteen (18) years and not before; ii) every other person shall be deemed to have attained his majority when he shall have completed his age of 21 years not before [16].…”
Section: Volatility Uncertainty Complexity and Ambiguity (Vuca) On Ch...mentioning
confidence: 99%
“…Some studies also indicated that healthcare providers believe that parental consent needs to be sought before providing SRH services to young people [96], this will increase the risk of young people utilization of unsafe and illegal healthcare services in cases of abortion [97]. Although, Zainudin, et al [98] opined that young people below the age of 18 years are considered minors and have no capacity to provide consent, thus requiring parental consent before healthcare services are delivered to them. Also, some respondents stated that they don't access SRHS because some of the healthcare providers are older than them [81,82] and they feel uncomfortable speaking to a much older practitioner [36,73,99].…”
Section: Attitudes Of Healthcare Providersmentioning
confidence: 99%